The foundations of craft: A suggested protocol for introducing craft to other disciplines. Issue 1 (4th May 2012) - Kettley, Sarah
The influence of craft on Product Design practices can be seen in the growth of young start ups citing craftsmanship as a core value of their business, in the increasing attention paid to 'slow design', and in the use of craft tropes to sell mass produced products. This article presents seven 'foundations' of craft, an outcome of a programme of research in which contemporary craft was reflexively employed as a methodology for designing digital jewellery. It challenges the many disciplines of Design to engage with craft in a critically informed manner, and to understand the potential this approach holds for meaningful design. The article is organized into sections according to each of the seven principles proposed.